Bromelain enzyme assay using Casen as substrate - Amid, Azura; Jamaluddin, Mohd Jamil Aizat (IIUM Press, 2016)
This procedure is following Sigma's non-specific protease activity. In this assay, casein acts as a substrate to the reaction. When protease digest casein, the amino acid tyrosine is liberated along with other amino acids and peptide fragments. Folin & Ciocalteus Phenol, or Folin's reagent primarily reacts with free tyrosine to produce a blue colored chromophore, which is quantifiable and measured as an absorbance value on the spectrophotometer at 660 nm absorbance. The more tyrosine that is released from the casein, the more chromophores are generated and the stronger the activity of the protease.